Generalized Hardy Transformation and Toeplitz Operators in BMOA-Type Spaces - Shamoyan, R. F. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We study the action of the generalized Hardy transformation in the BMOA classes in a half-disk and present a criterion for the boundedness of the Toeplitz operators acting in a BMOA-type space in the unit disk.